You're not going to give me the umbrella, are you?. Issue 7582 (21st December 2006) - Bradbeer, C; Soni, S; Ekbote, A; Martin, T
Abstract : The "umbrella test" is a longstanding urban myth that still bothers men who present for testing at sexual health clinics